ORGANIZATIONAL JUSTICE AND AFFECTIVE COMMITMENT TO CHANGE IN EMPLOYEES OF MULTIFINANCIAL SERVICE COMPANY - Primawidi, Safitri; Mangundjaya, Wustari (Faculty of Psychology, Diponegoro University, 2020)
The aim of the study is to investigate the role of organizational justice to affective commitment to change. The study was conducted based on data collected from 42 employees working in head office of multifinancial service company. It is made up of 16 males and 26 females’ employees. Affective commitment to change was measured using Herscovitch and Meyer’s Affective Commitment to Change Scale (6 items; α= .828). While organizational justice was measured using Colquitt’s Organizational Justice Scale (20 items; α=.905). The hypotheses were tested using multiple regressions. The result showed R2 of .821, meaning that 82% of affective commitment to change can be explained by organizational justice. Among four dimensions of organizational justice, procedural justice has the most influence and significant role on affective commitment to change (β= .445, p<.001), followed by distributive justice (β = .336, p<.001). The findings of the study demonstrated that organizational justice has positive significant impact on affective commitment to change, particularly distributive and procedural justice. Based on this study, in order to develop affective commitment to change in these multifinance company employees, to design intervention to increase organizational justice is neccessary.